How people learn : brain, mind, experience, and school - Brandsford, John D.; Brown, Ann L.; Cocking, Rodney R.; Pellegrino, James W.; Donovan, M. Suzanne (National Academy Press, 2000)
Evaluates the most current scientific data on learning, teaching and learning environments. The objective of the book was to ascertain what is required for learners to reach deep understanding, to determine what leads to effective teaching and to evaluate the conditions that lead to supportive environments for teaching and learning. Six areas that are relevant to a deeper understanding of students' learning processes are explored: the role of prior knowledge in learning; plasticity and related issues of early experience upon brain development; learning as an active process; learning for understanding; adaptive expertise; and learning as a time-consuming endeavor. The book discusses research in another 5 areas that are relevant to teaching and environments that support effective learning: the importance of social and cultural contexts; transfer and the conditions for wide application of learning; subject matter uniqueness; assessment to support learning; and the new educational technologies.